An overview of domestic aspects in US climate policy - Ferreira, Solange Reis m; Ferreira, Kelly [UNESP]; Vigevani, Tullo [UNESP] (Inst Brasileiro Relacoes Int, 2012)
The article shows how domestic aspects influence the United States national and international climate policy. To accomplish the task, the authors analyzes the discussions when Bill Clinton was ruling the country, a time during which global discussions were forwarded. The paper recalls the debate in the Bush administration and the growing polarization since Barack Obama took office.
Uma visão geral dos aspectos domésticos da política climática dos EUA
Keywords: climate policy; domestic interests; United States